OpenFlow table lookup scheme integrating multiple-cell Hash table with TCAM - Chun-qiang LI; Yong-qiang DONG; Guo-xin WU (Tongxin xuebao)
In OpenFlow networks,switches accept flow rules through standardized interfaces,and perform flow-based packet processing.To facilitate the lookup of flow tables,TCAM has been widely used in OpenFlow switches.However,TCAM is expensive and consumes a large amount of power.A hybrid lookup scheme integrating multiple-cell Hash table with TCAM was proposed for flow table matching to simultaneously reduce the cost and power consumption of lookup structure without sacrificing the lookup performance.By theoretical analysis and extensive experiments,optimal capacity configuration of Hash table and TCAM was achieved with the optimized cost of flow table lookup.The experiment results also show that the proposed lookup scheme can save over 90% cost and the power consumption of flow table matching can be reduced significantly compared with the pure TCAM scheme while keeping the similar lookup performance.